Proton beam irradiation for non-AMD CNV: 2-year results of a randomised clinical trial. Issue 9 (12th May 2014) - Chen, Ling; Kim, Ivana K; Lane, Anne M; Gauthier, Danny; Munzenrider, John E; Gragoudas, Evangelos S; Miller, Joan W
Abstract : Aims: To evaluate safety and visual outcomes after proton beam irradiation (PBI) therapy for subfoveal choroidal neovascularisation (CNV) secondary to causes other than age-related macular degeneration (AMD). Methods: This study is a prospective, unmasked and randomised clinical trial using two dosage regimens, conducted in the Massachusetts Eye and Ear Infirmary. The study included 46 patients with CNV secondary to non-AMD and best-corrected visual acuity of 20/320 or better. Patients were randomly assigned to receive 16 or 24 cobalt gray equivalents (CGE) of PBI in two equal fractions. Complete ophthalmological examinations, fundus photography and fluorescein angiography were performed at baseline and 6, 12, 18 and 24 months after treatment. Results: At 1 year after treatment, 82% and 72% lost fewer than 1.5 lines of vision in the 16 CGE and in 24 CGE groups, respectively. At 2 years after therapy, 77% in the lower dose group and 64% in the higher dose group lost fewer than 1.5 lines of vision. Mild radiation complications such as radiation vasculopathy developed in 17.6% of patients. Conclusions: PBI is a safe and efficacious treatment for subfoveal CNV not due to AMD. The data with respect to visual outcomes and radiation complications trend in favour of the 16 CGE group, although differences do not reach statistical significance. PBI may be considered as an alternative to current therapies.